SIMPTOM MIMPI HISTERIA RASUKAN JIN DALAM PERSPEKTIF PESAKIT, PERAWAT DAN HADIS(NIGHTMARES SYMPTOM OF HYSTERIA UNDER EVIL POSSESSION FROM THE PERSPECTIVES OF PATIENTS, THERAPISTS AND ISLAMIC TRADITION) (UMRAN - Journal of Islamic and Civilizational Studies, 2015)
This study aims at specifying nightmares symptom of hysteria under evil possession from the perspectives of patients, therapists and Islamic Tradition of the Prophet P.B.U.H. Cases studied is on the common hysteria incidents including type of hysteria like normal possession al-sar’ or al-mass, saka and withcraft hysteria. An interview survey and observation were carried out towards patients and therapists in gathering informations. The result of qualitative study is analysed thematically after a coding was done using Atlas ti. 7 Software. Experts agree to carry out on stated theme using Cohen Kappa’s calculation method. Content analysis also was done to evaluate nightmare symptom of evil possession on Islamic tradition perspective. Finding shows that there were specific forms of nightmare as an evil possession symptom. This characteristic of nightmares causes sense of pain at the whole body in the next morning.  Patients having nightmares before ruqyah treatment. Beside that, patients’ nightmare lessens and disappears after receiveing ruqyah treatment. Symptom of behavior, physical and experience during treatment such as screaming, trembling, eyes shaking, and delusion also differentiate between hysteria evil possession from hysteria psychological disorder and evil temptation. This is due to the ruqyah treatment from al-Quran and prophet’s recitement affected towards evil. It is too difficult to differentiate nightmare simptom among normal evil possession, saka and witchcraft because the most of nightmare symptom were the same as hysterical evil possession symptom.
Keywords: Symptom; nightmares; hysteria; evil possession; patient; therapist; Islamic traditions